Visualization of Fluoroscopic Imaging in Orthopedic Surgery: Head-Mounted Display vs Conventional Monitor. (June 2022) - Johnson, Alex A.; Reidler, Jay S.; Speier, William; Fuerst, Bernhard; Wang, Jiangxia; Osgood, Greg M.
Purpose . See-through head-mounted displays (HMDs) can be used to view fluoroscopic imaging during orthopedic surgical procedures. The goals of this study were to determine whether HMDs reduce procedure time, number of fluoroscopic images required, or number of head turns by the surgeon compared with standard monitors. Methods . Sixteen orthopedic surgery residents each performed fluoroscopy-guided drilling of 8 holes for placement of tibial nail distal interlocking screws in an anatomical model, with 4 holes drilled while using HMD and 4 holes drilled while using a standard monitor. Procedure time, number of fluoroscopic images needed, and number of head turns by the resident during the procedure were compared between the 2 modalities. Statistical significance was set at P < .05. Results . Mean (SD) procedure time did not differ significantly between attempts using the standard monitor (55 [37] seconds) vs the HMD (56 [31] seconds) ( P = .73). Neither did mean number of fluoroscopic images differ significantly between attempts using the standard monitor vs the HMD (9 [5] images for each) ( P = .84). Residents turned their heads significantly more times when using the standard monitor (9 [5] times) vs the HMD (1 [2] times) ( P < .001). Conclusions . Head-mounted displays lessened the need for residents to turn their heads away from the surgical field while drilling holes for tibial nail distal interlocking screws in an anatomical model; however, there was no difference in terms of procedure time or number of fluoroscopic images needed using the HMD compared with the standard monitor.